2021
DOI: 10.1103/physrevb.104.134501
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of high- Tc superconductivity in ternary lanthanum borohydrides

Abstract: The study of superconductivity in compressed hydrides is of great interest due to measurements of high critical temperatures (T c ) in the vicinity of room temperature, beginning with the observations of LaH 10 at 170-190 GPa. However, the pressures required for synthesis of these high-T c superconducting hydrides currently remain extremely high. Here we show the investigation of crystal structures and superconductivity in the La-B-H system under pressure with particle-swarm intelligence structure-searches met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…Note: While in preparation, we have become aware of four publications that attempt to explain our finding (Ge et al, 2021;Guan et al, 2021;Liang et al, 2021;Di Cataldo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Note: While in preparation, we have become aware of four publications that attempt to explain our finding (Ge et al, 2021;Guan et al, 2021;Liang et al, 2021;Di Cataldo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…59 As far as we know, P 6 3 / mcm K 2 ReH 9 becomes the highest- T c conventional superconductor among the pressurized ambient-pressure compounds, comparable to the predicted 126–138 K of LaBH 8 at 50 GPa, a famous low-pressure superconducting hydride. 63 By inspecting the change of λ and ω log , two main parameters for determining T c value, it is apparent that λ plays a dominant role in the T c evolution with pressure while ω log presents an opposite trend. Further, the elevated EPC with lowering pressure can be attributed to synergetic promotion of electron and phonon evolution.…”
Section: Resultsmentioning
confidence: 99%
“…But then multi-component hydrides contain more combinations of elements, they are more promising in the search for high(room)-temperature superconductivity. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] For example, magnesium hydride can dissociate the H 2 molecule into atomic H by lithium doping, thus increasing its electron concentration at the Fermi level (E F ), enabling it to reach a T c value of 473 K at 250 GPa. [47] Furthermore, recent research has revealed that a small amount of carbon doping in H 3 S can result in room superconductivity (T c = 287.7 ± 1.2 K at 267 ± 10 GPa).…”
Section: Introductionmentioning
confidence: 99%